A eficiência energética, a informação e a qualidade total da energia elétrica no modelo em desregulamentação - Colusso, Paulo Roberto (2003)
The tools of the Total Quality bring the Efficiency Energy availablely and moving electric energy for the productive sections and a better life quality to the final user. This work evidences that the knowledge (information, data) widespread ally the energy administration and new technologies, it largely alleviates the growing environmental impact for the energy use that the economic growth of the nations imposes. With the information, readjust of resources, with the tools of the quality and with the adapted use of the equipments that they compose an electric installation, more electric energy is disposed for the economic segments than today present use restrictions for the eminent lack of the energy resources that the world accuses. With the information and administration as tools of the quality, equation the offer is sought and it seeks of the energy for the efficient dispose of the electric energy and the rationalization is continue looked of its use with an idea of preservation of the environment. The data available of Cooperativa of Energy and Rural Development Coprel Ltda, Ibirubá, RS – Coprel, of its feeders that provision of electric energy the area of High Jacuí and Medium Plateau of the State of Rio Grande do Sul, Brazil, identifies evidences that take to believe that the lack of knowledge of the product Electric Energy, is one of the factors of its bad use, even so of high speed and answer efficiency as it was evidenced by the period in 2001 that the Camera of Administration of the Crisis of Electric Energy – MME acted.